Pengaruh Pergaulan Teman Sebaya Terhadap Perilaku Konsumtif Siswa Kelas IX MTs Miftahul Huda Bekasi - Anisa Nurul Sapna; Yon AE; Luluh Abdillah Kurniawan (Indo Publishing, 2025)
The background of this research is based on the phenomenon of the increasing consumptive behavior among adolescents, which is not only influenced by internal factors but also by external factors such as peer group interaction. The research method employed is a quantitative method with a descriptive approach. The population in this study consisted of all 9th-grade students of MTs Miftahul Huda Bekasi, totaling 40 students, with the sampling technique using total sampling. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis was carried out using descriptive statistics and simple linear regression with SPSS version 26. The results of the study show that peer interaction has a positive and significant effect on students’ consumptive behavior. This is evidenced by the regression coefficient value of 0.427, a t-count of 3.729 with a significance value of 0.001 < 0.05, as well as an F-count of 13.905 with a significance value of 0.001 < 0.05. The coefficient of determination (R Square) is 0.268, which means that 26.8% of the variation in students’ consumptive behavior is influenced by peer interaction, while the remaining 73.2% is influenced by other factors outside the scope of this research. Thus, the higher the intensity of peer interaction, the higher the level of students’ consumptive behavior. The results of this research are expected to provide input for teachers, parents, and schools in guiding students to develop a wiser and more controlled consumption pattern